PENGARUH SARAPAN TERHADAP KONSENTRASI BELAJAR MAHASISWA - Teteh Rima; Iwan Ridwan Yusuf; Sofiatun Nisa; Vinna Aulia; Tuti Kurniati (Pedagonal : Jurnal Ilmiah Pendidikan, 2020)
EFFECT OF BREAKFAST ON THE STUDENT LEARNING CONCENTRATIONBreakfast is a human need that is needed regularly every morning, for nutritional needs and brain development for students which should start early. The reduced concentration of learning one of which is influenced by the lack of nutrition in students. Student activities on campus will be disrupted if nutritional needs are not met. Nutritional problems that occur in Indonesia are still very many, one of which is Protein Energy Deficiency which greatly affects the concentration and ability of students to think. Measuring nutritional status is one aspect that very important so that no complications occur, namely malnutrition. So it is necessary to study specifically about how to keep the concentration of learning maintained to achieve goals that link the effect of breakfast on learning concentration and the impact on body health. The research design used is correlational research. The population in this study were all semester 7 Biology Education students.The sampling method was purposive sampling, through testing the results of questionnaires related to breakfast or no breakfast. Based on the results of the study found that there was an influence of breakfast on the concentration of 7th semester Biology Education students.